The effect of local anesthetics against planktonic forms and film formation of S. aureus strains and its dependence on antiseptics activity - Faustova, Mariia; Nazarchuk, Oleksandr; Dmytriiev, Dmytro; Babina, Yuliana; Nazarchuk, Halyna; Dudar, Alina (Frontiers in Microbiology, 2023)
Today surgical site infections (SSIs) remain the second among hospital acquired infections in Europe and the USA. Staphylococcus aureus as a pathogen of nosocomial infections occur more frequently in surgical hospitals. The work was aimed to establish the effect of local anesthetics against planktonic forms and biofilm-formation of S. aureus clinical strains and the relationship between the sensitivity of S. aureus strains to local anesthetics and antiseptics in vitro. The antimicrobial activity of local anesthetics (0.5%, bupivacaine, 2.0% lidocaine, 0.375% ropivacaine) and antiseptics (decamethoxine 0.02 %, chlorhexidine 0.05%) against clinical strains of S. aureus was observed and studied their ability to produce biofilms. The antimicrobial effect of local anesthetics was lower compared to antiseptics, but we observed inhibition of growth and reproduction of S. aureus in their presence. The ropivacaine solution and the lidocaine solution demonstrated almost the same activity against the studied microorganism isolates. Along with this, bupivacaine solution had the highest activity against the studied microorganisms. The minimal inhibitory concentration of bupivacaine for S. aureus was 2.2 times lower than the minimal inhibitory concentration of lidocaine and 2.1 times lower than the minimal inhibitory concentration of ropivacaine significantly (p < .05). Scientific research on various aspects of the formation of bacterial biofilms is a relevant area that will change approaches to the prophylaxis and treatment of a number of infections, including SSIs